The Role of Carbon Dioxide in the Rat Acute Stroke Penumbra - Yeo, Leonard L.; Arnberg, Fabian; Chireh, Arvin; Sharma, Vijay; Tan, Benjamin; Gontu, Vamsi; Little, Philip; Holmin, Staffan (Frontiers in Digital Health, 2022)
Purpose—The vasodilatory response to inhaled CO2 occurs in the acute stroke ischemic penumbra and may be a potential therapeutic modality. Methods—Twenty-two Sprague-Dawley rats were subjected to 90-mins occlusion of the M2 segment of the middle cerebral artery (M2CAO) by endovascular technique. The animals were administered different C02 concentrations and scanned serially with 9.4 T MRI. Infarct tissue was determined by diffusion-weighted imaging (DWI) and hypoperfused tissue was determined by arterial spin labeling (PWI). Results—4 animals were administered room air (RA)+ 6% CO2 (group 1), 6 animals RA+12% CO2 (Group 2) and 4 animals only RA (group 3). In the rats with CO2 administered (groups 1 and 2), the DWI lesion to cerebral hypoperfusion volume ratio (SD) at pre-CO2 administration, was 0.145(0.168), which increased to 0.708(0.731) during CO2 administration and reduced to 0.533(0.527) post-CO2 administration. In 9 of 10 rats the hypoperfused volume decreased when CO2 was administered. When CO2 was stopped the hypoperfused volume became larger again. Administration of RA+12% CO2 (Group 2) decreased the volume of CBF hypoperfusion significantly compared to the control group (95%CI: 0.084 ± 0.0213, p= 0.004). Conclusion Inhaled CO2 appears to reduce the size of the hypoperfused tissue volume during acute stroke and may be a potential modality for treatment of acute ischemic stroke. These findings will nonetheless need to be validated in a larger cohort in other centers.